HUBUNGAN ANTARA HIPERTENSI DAN KADAR KOLESTEROL DENGAN PENYAKIT JANTUNG KORONER (PJK ) DI RSUD BESEMAH PAGAR ALAM - Minata, Fika; Irawanza, Megi (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2019)
Coronary heart disease is a narrowing of the coronary arteries due to plaque accumulating in the inner walls of the coronary arteries, blood vessels that function to supply oxygen, and food substances to the heart muscle. This study aims to determine the relationship between hypertension and cholesterol levels with coronary heart disease. This research was carried out by taking medical record data in patients with CHD in the Besemah Pagar Alam Hospital in 2017, namely 45 people. This research is an analytical survey with a cross sectional approach, in the sense of taking Independent Variable data (hypertension and cholesterol levels) and Dependent Variables (Coronary Heart) carried out simultaneously. In this study respondents who were positive for coronary heart disease were 27 respondents (60%) out of 45 respondents. From the chi-square statistical test obtained (p value = 0.01 <? 0,05 stated that there was a relationship between hypertension and coronary heart disease and there was a correlation between cholesterol levels and coronary heart disease, where it was obtained (p value = 0.038) smaller than ? 0 The conclusion of this study is that there is a significant relationship between hypertension and coronary heart disease and there is a significant relationship between cholesterol levels and coronary heart disease.The suggestion of this study is to provide quality services and provide information to the community by means of counseling so that people know how how to prevent coronary heart disease.Keyword : coronary heart disease, hypertension and cholesterol levels.